A Comparative Study Between Single Dose & Multiple Doses of Mitomycin-C in the Management of Transitional Cell Carcinoma of Urinary Bladder (Bangladesh Journal of Urology, 2020)
Objectives: To find out the efficacy of post TURBT immediate single dose adjuvant intravesical Mitomycin C therapy in comparison with multi-dose regimen of Mitomycin C therapy in the management of superficial transitional cell carcinoma of the urinary bladder.Methods: Total 76 patients of bladder mass were included in the study who had undergone transurethral resection followed by immediate single instillation of Mitomycin C. After availability of histopathological examination report of resected tumor, those fulfill the selection criteria were randomized into two groups. One group (Group A) was the odd numbers of the patients who already received immediate single intravesical instillation of Mitomycin C and another group (Group B) even number of the patients who received single dose of intravesical instillation of Mitomycin C immediately with additional 5 instillations (1 week interval for 5 weeks) and in whom prospective follow-up could be completed within next 12 monthsResults: The effect of single intravesical instillation of 40 mg of Mitomycin C (Group A) within 24 hours of TURBT with that of multiple doses (six doses) of Mitomycin C (Group B) in similar dose was insignificant.Conclusion: The efficacy of MMC single dose was similar to MMC multi-dose regimen with insignificant difference of side effect among the two groups (0% versus 6.25%).Bangladesh Journal of Urology, Vol. 20, No. 2, July 2017 p.74-77